Menstrual Leave Policy; Between Gender Sensitivity and Discrimination Against Female Workers - Widyani, I Dewa Ayu (Technium Business and Management, 2022)
The right to get a job and a decent job is a human right, that is why the concept of labor protection emerged. Job protection is specifically given to female workers. One of the special policies that protect female workers is the menstrual leave policy. The menstrual leave policy is a policy that should be appreciated; however, it turns out that this policy actually triggers discrimination against female workers. This research will discuss the basic considerations of special protection for female workers, normative provisions regarding menstrual leave for female workers and discriminatory practices in menstrual leave policies. The menstrual leave policy is the protection of workers and human rights. This policy is contained in Article 81 of the Law of the Republic of Indonesia Number 13 of 2003 concerning Manpower. In practice, female workers do not take menstrual leave because they have the potential to experience discrimination in the form of verbal violence and economic violence.